Diversidade genética entre genótipos de algodoeiro visando ampliação da variabilidade - Miranda, Melissa Cristina de Carvalho (2019)
The success of Brazilian cotton cultivation is mainly due to investment in research and production technology, highlighting the progress of breeding programs. In order to guarantee the continuous development of cultivars it is necessary to make use of the genetic resources available within the genus Gossypium; however, the current genotypes tend to present a narrow genetic base, and associated with the cultivation of similar germplasm in large areas, provide greater vulnerability to biotic and abiotic stresses. Thus, in order to obtain genetic gains and the identification of hybrid combinations of greater heterocyclic effect in cotton genotypes, it is necessary to know the genetic diversity of the base population and satisfactory agronomic performance. The objective of this work was to evaluate the genetic diversity among cotton genotypes of the main breeding programs in Brazil and to indicate the best hybrid combinations in order to increase the variability. The work was carried out under field conditions in Uberlândia (MG) in the 2017/2018 harvest. The experiment was conducted in a completely randomized block design with 18 genotypes and three replicates. Three genotypes were selected from the breeding programs Embrapa, Monsanto Deltapine, Fibermax, IMA, TMG and PROMALG UFU. Evaluations were made when the plants were in the fully developed phenological stages of 5 leafs (V5), appearance of the first bud (C1), in full bloom and full maturity, as well as determination of cotton yield and feather yield. The fiber quality characteristics, such as fiber length, uniformity of length, short fiber index, strength, elongation, micronaire and fiber maturity were also checked. Individual and multivariate analyzes of variance were performed, estimating the genetic divergence based on the multivariate procedures of generalized distance of Mahalanobis and grouping of the genotypes by the Tocher optimization methods, UPGMA and graphic dispersion by canonical variables. The correlation study between the characteristics with higher CVg/CVe ratio and the genotypic determination coefficient was performed. It was also determined the relative contribution of the characteristics to detect genetic divergence by Singh's methodology. Moderate genetic divergence was detected among genotypes from breeding programs in Brazil. Hybrids between genotypes BRS 433 and FM 980 are promising for obtaining segregating populations with genetic variability and greater productive potential, feather yield and fiber quality. Crosses between the genotypes developed by PROMALG with FM 980 are interesting to improve the quantity and quality of UFUJP-B, UFUJP-H and UFUJP-P fibers. The characteristics of fiber quality, maturity, micronaire and fiber elongation showed a greater contribution to the detection of genetic divergence.